Lithium exposure during embryonic stage affetcs heart and eye morphology in zebrafish larvae via changes in Transcription factor expression - Fakurazi, Sharida; Rahmi, Koyuki Atifa; Rohman, Mohammad Saifur; Khotimah, Husnul; Sujuti, Hidayat (A and V Publication, 2024)
Background: Lithium is a first-line treatment for Bipolar Affective Disorder in pregnant women, but it has a narrow therapeutic range and has been shown to cause teratogenic effects on the foetus. This study aimed to investigate the molecular mechanism of lithium–induced heart and eye malformation during organogenesis. Methods: Zebrafish (Danio rerio) was used as the animal model. Zebrafish embryos were exposed to LiCl with concentrations of 0 (control), 3, 30, and 300 mg/L from 1 hpf to 72 hpf. Expression of heart organogenesis-associated genes nkx2.5, nppa, and myl7, and Eye Field Transcription Factors six3a and rx3 were measured using qPCR. Heart and eye morphology were observed using light microscopy and assessed based on representative score assignment for zebrafish teratogenicity assay. Results: In heart organogenesis, LiCl caused significant upregulation of nkx2.5 expression and increased the incidence and severity of heart malformations and contractility malfunction in zebrafish larvae. In eye organogenesis, LiCl caused substantial downregulation of six3a expression and a significant increase in the incidence and severity of eye malformations in zebrafish larvae. Conclusions: LiCl exposure towards zebrafish during the embryonic period disrupted heart and eye organogenesis by changing the expression of transcription factors involved in the respective organogenesis processes.